Development Contextual Approach-Based Fraction Learning Media (MACAN) for Grade V Elementary School - Satwika, I Nyoman Cita; I Wayan, Wiarta; Anak Agung, Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2025)
The rapid development of 21st-century technology demands innovation in education; however, mathematics learning in elementary schools is still predominantly delivered through conventional lecture methods. This condition leads to low student motivation and difficulties in understanding concepts, particularly in fraction topics. This study aims to develop, validate, and analyze the effectiveness of a contextual approach-based mathematics learning medium (MaCan) for teaching equivalent fractions to fifth-grade elementary students. This research employed a Research and Development (R&D) design using the ADDIE development model. The subjects consisted of 13 fifth-grade students for limited trials, one subject matter expert, one media expert, and one classroom teacher. Data were collected using validation questionnaires and multiple-choice tests. The data were analyzed through descriptive qualitative, descriptive quantitative, and inferential statistical techniques using a t-test. The results indicated that the MaCan learning media achieved a “good” category in expert validation, media, content, and design, as well as in individual and small group trials. The effectiveness test showed a t-value of 6.578 > 1.782 at a 5% significance level, indicating that H₀ was rejected and Ha was accepted. Conceptually, this finding confirms that MaCan is effective in improving students’ learning outcomes. The study recommends integrating contextual, technology-based learning media as an innovative alternative to enhance the quality of mathematics education in elementary schools.